Low Prognostic Nutritional Index Correlates with Worse Survival in Patients with Advanced NSCLC following EGFR-TKIs - Sheng, Jin; Yang, Yun-Peng; Ma, Yu-Xiang; Qin, Tao; Hu, Zhi-Huang; Hong, Shao-Dong; Zhou, Ting; Huang, Yan; Zhao, Hong-Yun; Zhang, Li (PloS one, 2016)
This study was designed to demonstrate the prognostic value of prognostic nutritional index (PNI), a reflection systemic immunonutritional status, on the long-term survival of patients taking epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs). In this retrospective study, eligible advanced NSCLC patients with sensitive EGFR mutations (exon 19 deletion or L858R in exon 21) were included to investigate the correlation between the PNI and overall survival (OS). The PNI was calculated as 10 x serum albumin value (g/dl) + 0.005 x peripheral lymphocyte count (per mm3). The prognostic significance of PNI and other clinicopathologic factors was identified by univariate and multivariate analysis. Finally, 144 patients met the inclusion criteria. The optimal cut-off value of PNI for survival stratification was 48.78. Compared with high PNI group (n = 81), low PNI (n = 63) was significantly associated with elevated C-reactive protein (CRP) level and non-response to TKIs. Overall survival was superior in the high PNI group (HR, 0.44, p = 0.004), especially for patient with L858R (HR, 0.37, p = 0.009) rather than 19 deletion (HR, 0.69, p = 0.401). The independent prognostic value of PNI was validated by multivariate analysis. This pilot investigation demonstrated that low prognostic nutritional index correlates with worse survival for patients with advanced NSCLC and taking EGFR-TKIs. The assessment of a convenient index, known as PNI, worth attention in routine clinical practice for patients following EGFR-TKIs treatment.